The Influence of The Agricultural Sector on Poverty in The Gerbangkertosusila Area: Agricultural Sector and Poverty in Gerbangkertosusila - Azim, Moh. Khoirul; Priyanto, Moh. Wahyudi (Journal of Tropical Rural Development, 2025)
Background and purpose – This study examines the role of the agricultural sector in poverty reduction in the Gerbangkertosusila region, Indonesia, where the sector is a key economic driver but poverty rates remain high. The research aims to analyze the impact of agricultural GRDP, population, dependency ratio, and urban population ratio on poverty levels. Methodology – A quantitative method with a panel data approach was used, utilizing secondary data from the Central Statistics Agency (BPS) and relevant sources. The analysis was conducted using panel data regression. Findings – The results indicate that agricultural GRDP has a significant negative effect on poverty levels, while the dependency ratio has a positive significant effect. Population and urban population ratio showed no significant effect. Additionally, industrial GRDP had a highly significant negative impact on poverty levels. Implications – The findings suggest that enhancing productivity and output in both the agricultural and industrial sectors is key to reducing poverty. Policymakers should prioritize infrastructure development in agriculture and investment in the industrial sector. Originality – This study provides critical insights into the relationship between sectoral economic growth and poverty reduction in a key Indonesian region, highlighting the joint role of agriculture and industry in poverty alleviation.